![(2-6s)(-5)=30s-10_{}](https://img.qammunity.org/2023/formulas/mathematics/high-school/onebxw196w09v5jwtwwwua571iix70du0t.png)
Here, we want to use the distributive property
To use this, the operator at the middle of the two initial terms will tell us the sign to use
Looking at the first expression, we can see a negative sign between 2 and -6s
Thus, in this case, when using the distributive property, we proceed as follows;
![\begin{gathered} (2-6s)(-5)\text{ = (2}*(-5))\text{ - (6s}*(-5)) \\ =\text{ -10 - (-30s)} \\ =\text{ -10 +30s = 30s-10} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/11mwsmp9ocjxcvsbi7nzgffurh1k5i0t1f.png)